2013
DOI: 10.1038/labinvest.2013.69
|View full text |Cite
|
Sign up to set email alerts
|

M2-polarized tumor-associated macrophages promoted epithelial–mesenchymal transition in pancreatic cancer cells, partially through TLR4/IL-10 signaling pathway

Abstract: M2-polarized tumor-associated macrophages (TAMs) are key regulators of the link between inflammation and cancer. A negative correlation between infiltration intensity of M2-polarized TAMs and prognosis of pancreatic cancer has been reported. Epithelial-mesenchymal transition (EMT) is an important biological process in the progression of primary tumors toward metastasis. Inflammation-induced EMT has been previously shown, therefore, we hypothesized M2-polarized TAMs could induce EMT in pancreatic cancer. Toll-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
290
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(323 citation statements)
references
References 25 publications
15
290
2
4
Order By: Relevance
“…33 Importantly, these M2c macrophages have been shown to promote epithelial-mesenchymal transition in pancreatic cancer cells, partially through TLR4/IL-10 signaling pathway. 34 Consistent with this, we found a profound upregulation in EMT markers (vimentin, N-cadherin) in DEN C HF-HC-HSD mouse livers that showed the M2 macrophage phenotype. Based on their IL-10 high IL-12 low profile, the M2 macrophages in our experimental model resemble the M2c subtype.…”
Section: Discussionsupporting
confidence: 87%
“…33 Importantly, these M2c macrophages have been shown to promote epithelial-mesenchymal transition in pancreatic cancer cells, partially through TLR4/IL-10 signaling pathway. 34 Consistent with this, we found a profound upregulation in EMT markers (vimentin, N-cadherin) in DEN C HF-HC-HSD mouse livers that showed the M2 macrophage phenotype. Based on their IL-10 high IL-12 low profile, the M2 macrophages in our experimental model resemble the M2c subtype.…”
Section: Discussionsupporting
confidence: 87%
“…43,44 In particular, it has been reported that tumorassociated macrophages were found at signifi cant concentrations within the region of tumor budding at the tumor invasive front 22 and that they promoted cancer cell invasiveness via epithelial mesenchymal transition. [23][24][25] Figure We did not perform colocalization studies on the same slide using immunofl uorescent techniques, which was a limitation of our study. However, our prospective investigation of the invasive tumor edge and associated immune cells may help us better understand biologic mechanisms that underlie this association.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] More importantly, studies have demonstrated that tumor-associated macrophages-especially those of the tumor-promoting M2 phenotype-are frequently found within regions of tumor budding 22 and that they have contributed to induction of cancer cell epithelial mesenchymal transition at the tumor invasive front. [23][24][25] Prognostic signifi cance of tumor budding and its correlation with immune factors have yet to be investigated in early-stage lung adenocarcinoma. We demonstrated that stromal forkhead box P3 (FoxP3)/CD3 lymphocyte risk index, tumoral IL-7 receptor (IL-7R) overexpression, and loss of tumoral IL-12 receptor b 2 (IL-12R b 2) expression were independent prognostic factors of stage I lung adenocarcinoma.…”
Section: [ 1 4 8 # 3 C H E S T S E P T E M B E R 2 0 1 5 ]mentioning
confidence: 99%
“…It is also important to note that a number of studies have analyzed the response of human cells to murine RAW 264.7 cells, with results that frequently replicate key features of disease pathology. [85][86][87][88][89][90][91][92][93] Future studies will use primary human macrophages to further develop this coculture system. Eventual testing of new therapeutics, particularly those targeting macrophage activation, using our developed coculture system will also be a key focus of future work.…”
Section: Discussionmentioning
confidence: 99%